Corporate Restructuring: Managing the Change Process from Within. - Denis, David J.; Donaldson, Gordon (Journal of Finance, 1995)
Corporate Restructuring examines the impact of financial restructuring on corporate priorities and performance. Countering the notion that an actual or threatened hostile takeover is needed to induce managers to restructure their firms, Donaldson claims that many companies have successfully restructured voluntarily. Drawing on a series of field studies and close examinations of three companies - General Mills, Burlington Northern, and CPC International - Donaldson shows how firms have implemented radical change through an internal discipline. The factual evidence demonstrates why and how voluntary restructuring works just as well - indeed better - than hostile takeovers, without the trauma of external intervention and disruption to day-to-day operations. Challenging many assumptions of current financial literature on how firms achieve increased efficiency, this book is bound to provoke controversy.